The art of wireless sensor networks - Ammari, Habib M. (Berlin : Springer, 2014)
During the last one and a half decades, wireless sensor networks have witnessed significant growth and tremendous development in both academia and industry. The Art of Wireless Sensor Networks: Volume 1: Fundamentals focuses on the fundamentals concepts in the design, analysis, and implementation of wireless sensor networks. It covers the various layers of the lifecycle of this type of network from the physical layer up to the application layer. Its rationale is that the first volume covers contemporary design issues, tools, and protocols for radio-based two-dimensional terrestrial sensor networks. All the book chapters in this volume include up-to-date research work spanning various classic facets of the physical properties and functional behavior of wireless sensor networks, including physical layer, medium access control, data routing, topology management, mobility management, localization, task management, data management, data gathering, security, middleware, sensor technology, standards, and operating systems.
v. 1. Fundamentals - v. 2. Advanced topics and applications.
Includes bibliographical references.
Keywords: Wireless sensor networks